2006
DOI: 10.1021/ac060985o
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Spectroscopy with a Variable Multivariate Optical Element

Abstract: Here, successful realization of a variable multivariate optical element (VMOE) based on a transmissive liquid crystal (LC) panel is reported. In contrast to conventional multivariate optical elements (MOEs), a single VMOE is a dynamic system, allowing measurement of numerous analytes in different mixtures. Furthermore, VMOE has superior spectral resolution in comparison to a conventional MOE. It is demonstrated here that the system implemented in a Raman spectrometer predicts the concentration of each individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…In spontaneous Raman spectroscopy, chemometric methods have been used for understanding hydrogen bonding 21 , detection of glucose levels 22 and bone degeneration 23 , and imaging of cells 24 . While these methods were used to analyze spectra computationally after data acquisition with a multi-element detector, recently multivariate optical computation employed a tailored multiband color filter in front of a single-element detector 25,26 . STE-SRS shares the same spirit, but tailors the excitation rather than emission spectra.…”
Section: Discussionmentioning
confidence: 99%
“…In spontaneous Raman spectroscopy, chemometric methods have been used for understanding hydrogen bonding 21 , detection of glucose levels 22 and bone degeneration 23 , and imaging of cells 24 . While these methods were used to analyze spectra computationally after data acquisition with a multi-element detector, recently multivariate optical computation employed a tailored multiband color filter in front of a single-element detector 25,26 . STE-SRS shares the same spirit, but tailors the excitation rather than emission spectra.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several previous studies have shown that chemometric techniques could be incorporated directly into the optical measurement process by using either static optical interference filters, 7 or tunable liquid crystal [8][9][10] or micromirror [11][12][13][14][15] based multivariate optical elements built into the spectrometer hardware. The general principle of these filters is to combine photons of various frequencies in a prescribed way in order to facilitate the estimation of a quantity of interest.…”
Section: -6mentioning
confidence: 99%
“…As the Raman cross section is relatively weak, this methodology requires typically long acquisition times to overcome noise associated with detection hardware. To overcome these limits, new strategies have been recently implemented, mostly focused on spectrally multiplexed measurements that may enable faster or shot-noise limited performance [1][2][3][4][5][6]. Nevertheless, these "full spectrum" multiplexing methodologies still acquire data which might be not necessary for certain applications, such as in sorting chemical species whose Raman spectra are known.…”
Section: A Introductionmentioning
confidence: 99%